The Authority Of Property And Heritage Agency Regarding Making Of Inheritance Certificate For The Decendant Of East Asian - Nova Winantika Rindang Kirana; I Nyoman Nurjaya; Herman Suryokumoro (Faculty of Law, University of Mataram, 2019)
This study aims to know and analyze which norms are enacted in the making of inheritance certificate and to know the strength of law in the certificate of inheritance made by Property and Heritage Agency after the enactment of Law No. 23 of 2006 on Population Administration. The research method used by the writer is statute approach and conceptual approach. The basis of the authority of Property and Heritage Agency is not in accordance with the state of the nation at this time and also based on the hierarchy of legislation is lower than the position of Law No. 23 of 2006. In addition, the certificate of inheritance made by the Property and Heritage Agency does not guarantee certainty and legal protection for Indonesian citizens because the strength of proof is not as perfect as the deed of inheritance made by the Notary.